Building sport policy's legitimacy in Norway and New Zealand. (August 2018) - Sam, Michael P.; Tore Ronglan, Lars
Governing state-funded sport is tenuous because of the need to maintain legitimacy and support from political authorisers, stakeholders and network partners/members. The purpose of this paper is to compare/contrast how central sport agencies in Norway and New Zealand create, build or sustain legitimacy through their accountability regimes. More particularly, this comparison distinguishes between input and output sources of legitimacy, where the former is associated with democratic processes (e.g., electoral procedures and public consultation), and the latter is linked with results and demonstrable benefits. While the Norwegian Olympic and Paralympic Committee and Confederation of Sports (NIF) draws legitimacy from its representative membership structures and status as a social movement, Sport New Zealand claims legitimacy on the basis of achieving targets and outputs. In both cases there are emerging pressures to recast input–output legitimating narratives, suggesting their 'depleteability' over time. These shifts are discussed in relation to their influence on policy reforms within environments of accountability that are fluid and incomplete.